2010
DOI: 10.1088/2040-8978/12/6/065601
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical characterization of Ag photo-doped thin As40S60 −xSexfilms for non-linear applications

Abstract: This paper deals with the structure and the optical properties of thin As40S60 − xSex films doped with silver. The refractive index n and the optical band gap Egopt were calculated from the transmittance and reflectance spectra. The results showed that the photo-doping leads to increase in the refractive index by about 0.25–0.27. An effect of thickness expansion was observed in the photo-doped layers. The non-linear refractive index, γ, and the two-photon absorption coefficient, β, were evaluated by applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 69 publications
(96 reference statements)
3
13
0
Order By: Relevance
“…However, it is a common phenomenon with chalcogenide glassy semiconductors that many properties of bulks are dierent from those of the lms of the same composition. A similar value of the band gap for the lm of the glass As 40 S 30 Se 30 was also reported by some other authors (2.01 eV) [6,7] and (2.08 eV) [8]. The same trend of the change in the value of E g with silver doping was also found in some other systems such as AgAsSe [9], AgAsS [10] and AgAsSSe [1,11].…”
Section: Resultssupporting
confidence: 88%
“…However, it is a common phenomenon with chalcogenide glassy semiconductors that many properties of bulks are dierent from those of the lms of the same composition. A similar value of the band gap for the lm of the glass As 40 S 30 Se 30 was also reported by some other authors (2.01 eV) [6,7] and (2.08 eV) [8]. The same trend of the change in the value of E g with silver doping was also found in some other systems such as AgAsSe [9], AgAsS [10] and AgAsSSe [1,11].…”
Section: Resultssupporting
confidence: 88%
“…It is observed that for the entire spectral range, the refractive index increases with the increasing Ag concentration. Similar results for Ag doped ternary thin films are reported [31][32][33] in the literature. The accuracy of the refractive index may be increased by calculating the film thickness using basic interference equation…”
Section: Refractive Index Film Thickness and Extinction Coefficientsupporting
confidence: 91%
“…Compositional variation of the refractive index and optical band-gap of chalcogenide glass thin films. The data depicted is taken from own studies and published elsewhere (Todorov et al, 2001(Todorov et al, , 2003Tasseva et al, 2005Tasseva et al, , 2007Tasseva et al, , 2010Kincl et al, 2009;Knotek et al, 2009;Petkov et al , 2009). …”
mentioning
confidence: 99%